Nanocrystallized Ge-Rich SiGe-HfO2 Highly Photosensitive in Short-Wave Infrared - Palade, Cătălin; Lepădatu, Ana-Maria; Slav, Adrian; Teodorescu, Valentin Șerban; Stoica, Toma; Ciurea, Magdalena Lidia; Ursuțiu, Doru; Samoilă, Cornel (MDPI AG, 2021)
Group IV nanocrystals (NCs), in particular from the Si–Ge system, are of high interest for Si photonics applications. Ge-rich SiGe NCs embedded in nanocrystallized HfO2 were obtained by magnetron sputtering deposition followed by rapid thermal annealing at 600 °C for nanostructuring. The complex characterization of morphology and crystalline structure by X-ray diffraction, μ-Raman spectroscopy, and cross-section transmission electron microscopy evidenced the formation of Ge-rich SiGe NCs (3–7 nm diameter) in a matrix of nanocrystallized HfO2. For avoiding the fast diffusion of Ge, the layer containing SiGe NCs was cladded by very thin top and bottom pure HfO2 layers. Nanocrystallized HfO2 with tetragonal/orthorhombic structure was revealed beside the monoclinic phase in both buffer HfO2 and SiGe NCs–HfO2 layers. In the top part, the film is mainly crystallized in the monoclinic phase. High efficiency of the photocurrent was obtained in a broad spectral range of curves of 600–2000 nm at low temperatures. The high-quality SiGe NC/HfO2 matrix interface together with the strain induced in SiGe NCs by nanocrystallization of both HfO2 matrix and SiGe nanoparticles explain the unexpectedly extended photoelectric sensitivity in short-wave infrared up to about 2000 nm that is more than the sensitivity limit for Ge, in spite of the increase of bandgap by well-known quantum confinement effect in SiGe NCs.
Keywords: group IV nanocrystals; HfO2; magnetron sputtering; rapid thermal annealing; SWIR; spectral photocurrent